Students' Mathematical Understanding Ability On The Material Of The Linear Absolute Value Of One Variable Assisted By A Digital Module - Pujakusuma, Gina Kustina; Pramuditya, Surya Amami (Universitas Wiralodra, 2023)
Mathematical understanding ability is an ability that is considered important for students because it is the basis for other mathematical abilities. However, it turns out that students' mathematical comprehension ability is still low, especially in the part of linking between concepts. The problem must be solved so that the student does not have difficulties in receiving the material. To solve this problem, researchers choose teaching materials in the form of digital modules that are considered capable of improving mathematical understanding skills. This research uses a qualitative approach with a case study method. Data collection is carried out by means of interviews, tests, and observations. Data processing is carried out by means of reduction, presentation and drawing conclusions. The data is presented in the form of a qualitative description. The results showed that digital modules are practical and usable. However, it is inversely proportional to the mathematical comprehension ability of students who are still in instrumental understanding, including: 1). Understanding the material, 2). Mentioning examples and not examples, 3). Explaining using its own language, 4). Draw conclusions for simple questions but have not been able to have a good impact on students in terms of linking between concepts. So that the existence of digital modules is still unable to solve the problem of low relational understanding ability.